Alternative Approaches for Clinical Management of Hyperlipidemia - Khan, Moosa; Niaz, Khalid; Murad, Shah; Aslam, Hina (Biology, Engineering, Medicine and Science Reports)
For coronary artery disease (CAD), it is generally accepted that prevention is better than cure. Cessation of cigarette smoking, habitual alcohol ingestion, changing sedentary life habits, skipping intake of processed or dairy foods, regular exercise can prevent people for being victimized by CAD. If taking all possible efforts described above, someone is getting ill, then come on to take Vitamin B3 (Niacin) 2 grams daily and kalwanji or Nigella sativa. This study was conducted at National hospital, Lahore from 24 January 2016 to June 2016. It was single blind placebo-controlled study approved by ethics committee, National Hospital, Lahore. Ninety hyperlipidemic male/female patients age range from 22 to 60 years were selected from cardiology and medical wards of the hospital. They were divided in three groups, one at placebo therapy, another on Kalonji and third one on Vitamin B3 . After one and half month, significant changes (p value ranging from <0.05 to <0.001) were observed in their LDL and HDL-cholesterol as compared to pre and post-treatment values of placebo group. Conclusion of the study was to recommend use of herbal medicine and Vitamin B3 for prevention of any heart diseases with good patient compliance.
Keywords: Coronary artery disease